Utilizing the YouTube Channel “Jago Bahasa Indonesia” to Improve Indonesian Language Skills - Tety Rukmanah Rukmanah; Didah Nurhamidah (UIN Raden Mas Said Surakarta, Indonesia, 2025)
The rapid advancement of technology and information has brought various innovations to the field of education, one of which is the utilization of digital media such as YouTube as a learning platform. This study aims to describe the effectiveness of the YouTube channel